Efecto del metilparabeno en la integridad del ADN de las células del cúmulo de ovocitos porcinos - Ramírez Jara, Yenny Paola (Universidad Autónoma Metropolitana, 2024)
Parabens (PB) are a homologous series of groups derived from parahydroxybenzoic acid (PHBA), esterified at the C-4 position (including methyl-, ethyl-, propyl-, butyl-, ethyl- and benzylparaben) that are widely used as preservatives in personal care and food products due to their antibacterial and antifungal effect. They are frequently used alone or in combination, with methylparaben (MePB) being one of the most widely used PBs due to its high solubility. The widespread use of PBs results in exposures through a variety of routes, such as dermal absorption, ingestion and inhalation. This high exposure to PBs has guided several in vivo and in vitro studies to determine their toxic effect on various body systems, finding that PBs cause multiple alterations at the endocrine and reproductive levels. Therefore, the objective of this study was to evaluate the exposure of porcine oocytes to 500 µM, 750 µM and 1000 µM MePB concentrations by means of in vitro viability and maturation (IVM) and cumulus cell (CC) DNA viability and integrity. The results showed significant differences (p˂0.05) in the viability and maturation of oocytes in the group exposed to 1000 µM MePB concentration with respect to the control group. In the oocytes it was possible to evidence chromatin damage where significant differences were found in the group exposed to 1000 µM MePB. In the oocytes it was possible to evidence chromatin damage where significant differences were found in the group exposed to 1000 µM MePB. In the CC, DNA integrity was evaluated, differences were found in all groups (500, 750 and 1000 µM) with respect to the control group and viability where in the percentage of dead oocytes - dead granules (OM-CM) significant differences were also found in the 1000 µM MePB group with respect to the control group, which allowed elucidating the effect that MePB is causing in the CC. This effect is an important finding since no studies evaluating the effect of MePB on DNA integrity and viability of DCs have been reported. Key words: Methylparaben, in vitro maturation, cumulus cells, oocytes, porcine experimental model.; Los parabenos (PB) son una serie homóloga de grupos derivados del ácido parahidroxibenzoico (PHBA), esterificados en la posición C-4 (incluidos metil-, etil-, propil-, butil-, etil- y bencilparabeno) que se utilizan ampliamente como conservantes en productos de cuidado personal y conservantes de alimentos dado su efecto antibacteriano y antifúngico. Frecuentemente son usados solos o en combinación, siendo el metilparabeno (MePB) uno de los PB más utilizados por su alta solubilidad. El uso generalizado de PB da como resultado exposiciones a través de una variedad de vías, como la absorción dérmica, la ingestión e inhalación. Esta alta exposición a los PB ha orientado diversos estudios in vivo e in vitro para determinar su efecto tóxico en diversos sistemas del organismo, encontrando que los PB son causantes de múltiples alteraciones a nivel endocrino y reproductivo. Por lo tanto, el objetivo de este estudio fue evaluar la exposición de ovocitos porcinos a concentraciones de 500 µM, 750 µM y 1000 µM de MePB por medio de la viabilidad y maduración in vitro (MIV) y la viabilidad e integridad del ADN de las células del cúmulo (CC). En los resultados se encontraron diferencias significativas (p˂0.05) en la viabilidad y maduración de los ovocitos en el grupo expuesto a la concentración de 1000 µM de MePB con respecto al grupo control. En los ovocitos fue posible evidenciar daño en la cromatina donde se encontraron diferencias significativas en el grupo expuesto a 1000 µM de MePB. En las CC se evaluó la integridad del ADN, se encontraron diferencias en todos los grupos (500, 750 y 1000 µM) con respecto al grupo control y la viabilidad donde en el porcentaje ovocitos muertos – granulosas muertas (OMCM) también se encontraron diferencias significativas en el grupo de 1000 µM de MePB con respecto al grupo control, lo que permitió dilucidar el efecto que está causando el MePB en las CC. Este efecto es un hallazgo importante ya que no se han reportado estudios que evalúen el efecto del MePB en la integridad del ADN y viabilidad de las CC. Palabras clave: Metilparabeno, Maduración in vitro, células del cúmulo, ovocitos, modelo porcino.